BED SEDIMENT DISTRIBUTION IN THE RIVER ESTUARY AND COASTAL SEA OF MALILI (SOUTH SULAWESI, INDONESIA) - Lanuru, Mahatma; Yusuf, Syafyudin (Jurnal Ilmu Kelautan SPERMONDE, 2018)
Bed sediment characteristics and distribution is one of the important parameters in determining the management plan and utilization of estuarine and coastal waters.  The objective of this study was to analyze sediment distribution and determine dominant oceanographic factors controlling the distribution of bed sediment in the river estuary and coastal sea of Malili. Sediment samples were collected using a grab sampler at ten stations, namely four stations in the river estuary and six stations in the adjacent coastal sea for grain size and sediment organic content analysis. The results showed that the bed sediment along the river estuary consisted of silt, very fine sand, fine sand, and medium sand with organic content varying from 1.31 to 7.18 %. In the coastal sea, bed sediment was dominated by silt with a higher organic content of 2.25 - 7.31%